Marine palaeo-ecological and depositional processes on the shallow-waters of the Azores archipelago: the mobile Ostracoda (Crustacea) and the sessile Bryozoa as case-studies - Meireles, Ricardo Piazza (2013)
In this thesis I aimed to 1) undertake a taxonomic revision of the Fossil and Recent shallow (from the intertidal down to 100 m depth) Ostracoda and of the Recent shallow Bryozoa of the Azores; 2) describe the zonation of the Recent species of Ostracoda on the Azorean shores; 3) use the above-mentioned studies to compare with the palaeo-ecological studies that were done on the fossiliferous Late-Miocene-Early-Pliocene of the Santa Maria Island’s outcrops; 4) establish the palaeo-biogeographical relationships of the Recent and fossil ostracods; 5) produce a Reference Collection of the Bryozoa and Ostracoda which will be deposited at the Departament of Biology, Universtity of the Azores, in order to provide additional tools for identifying the more conspicuous species of Bryozoa and Ostracoda from the Azores. […].